Epigallocatechin-3-gallate protects cardiomyocytes from hypoxia-reoxygenation damage via raising autophagy related 4C expression - Ping Liu (Taylor & Francis Group, 2021)
Myocardial ischemia/reperfusion (I/R) injury is a serious issue during the therapy of myocardial infarction. Herein, we explored the beneficial influence of Epigallocatechin-3-gallate (EGCG) on hypoxia/reoxygenation (H/R)-stimulated cardiomyocyte H9c2 cells damage, along with possible internal molecular mechanism related autophagy related 4C (ATG4C). H9c2 cells were subjected to H/R stimulation and/or EGCG treatment. ATG4C mRNA expression was measured via q-PCR assay. ATG4C overexpression plasmid (OE-ATG4C) was transfected to arise ATG4C level. Cell viability, apoptosis, reactive oxygen species (ROS) production, ATP level were tested via CCK-8 assay, Annexin V-FITC/PI staining, DCFH-DA staining and ATP Assay Kit, respectively. Western blotting was performed to test Cleaved-caspase 3, Cleaved-caspase 9, cytochrome C and LC3B protein levels. H/R stimulation resulted in H9c2 cell viability loss, promoted cell apoptosis and ROS overproduction, as well as lowered ATP level in cells. EGCG treatment alleviated H/R-resulted H9c2 cell viability loss, cell apoptosis, ROS overproduction and reduction of ATP level. Moreover, H/R stimulation reduced the ATG4C expression in H9c2 cells, while EGCG raised the ATG4C expression. Overexpression of ATG4C strengthened the beneficial influence of EGCG on H/R-stimulated H9c2 cell viability, apoptosis and ROS production. Besides, ATG4C overexpression weakened the H/R-stimulated H9c2 cell autophagy via reducing LC3B II/I expression. EGCG exerted beneficial influence on H/R-stimulated cardiomyocytes, which protected cardiomyocytes from H/R-stimulated viability loss, apoptosis and ROS overproduction via enhancing ATG4C expression.